ANALISA MENINGKATKAN PERFORMANSI OPERASI BOILER TIPE FULTON 30E - Rufinus Nainggolan; Benar Surbakti (J-Innovation, 2018)
The boiler has been shown performance from a number of the transfer convension on energy to product gasses. The type of Fulton 30E, with analyizing capasitively on the 4,5,6,7 and 8 of the gasses quality. The analyzing which is operating the type of Fulton 30E boiler on testing in the Energy Laboratorium Engineering.at the Polytechnic of State Medan. The high pressure will being increasing higher eficiency of boiler’s gasses on 278.65 kg/m and 65,6 %. The conclusion boiler performance are must be maximum of higher pressure conditions.To increasing eficiency had to do the analyzing loses and designing heat recovery of it.